A Biblioteca Móvel da Susipe “Arca da Leitura”: práticas de leitura em ambiente prisional - MORAES, Manuela Carneiro de (2017)
It briefly discusses the stimulus of reading from childhood, school and family and the importance of reading as a source of knowledge. It also presents the importance of the prison library as the main instrument to help re-educate the victims. It also explains the situation of the penitentiary system and resocialization. It makes reference to Susipe- Superintendency of the Penitentiary System of the State of Pará, its mission, its function as body responsible for the penitentiary administration in the State of Pará and cites the existing prison units. It addresses the penalty of deprivation of liberty and the nomenclatures to designate one who has had his freedom suspended. Finally, he discusses the beginning of the Ark of the Reading Project, its strategy for making the bookshelves and the way to acquire material for the collection, its performance in the units contemplated by the project and its operation within the prison unit of the CRC- Coconut Recovery.